Government Expenditures On Education, Health, And Infrastructure : A Naive Look At Levels, Outcomes, And Efficiency - Trujillo Castellano, Lourdes (The World Bank, 2007)
All interested parties seem to agree that it is important to be able to monitor public sector performance at the sectoral level, but most current work based on multi-country databases does not lend itself to country-specific conclusions. This is due to a large extent to major data limitations both on sectoral expenditures and on sectoral outcomes. This paper discusses the related issues and shows what we can do with the current data inspite of the drastic limitations. The main conclusions of the paper are that any efforts to assess country-specific performances in relative terms are likely to be difficult in view of the data problems. A rough sense of performance across sectors can be estimated for groups of countries, allowing some modest benchmarking exercises. These estimates show that low-income countries generally lag significantly behind higher-income countries. Efficiency has improved during the 1990s in energy and education but has not improved significantly in transport